The city from the window of collective action - Quiroga, María Virginia (2016)
This article invites to look at the city from the window of collective action. It is a window with multiple edges, with transparencies and opacities too, always opened to questions and propositions. How to characterize the scenery of social organizations´ interaction in the local space? Which are their main objectives? Do they participate in any political project? What kind of relationships they established between themselves and with the territory? These are some of the questions that outlined the route of this article, also they encouraged us in the initiative of building a cartography of socio-territorial and socio-political organizations in Río Cuarto (Argentina) during the period 2014-2015.